Pendidikan Islam sebagai Fondasi Pembentukan Karakter Keluarga Sakinah Mawaddah Warahmah - Ainiyah, Qurrotul; Nurul Qomaria , Elysa (ILJ: Islamic Learning Journal, 2025)
This study examines the formation of a sakinah mawaddah warahmah family in the perspective of Islamic education as an effort to create a harmonious and happy family in this world and the hereafter. The study uses the library research method with data sources from relevant academic literature, analyzed through a descriptive-analytical and deductive approach with philosophical, socio-historical, and psychological perspectives. The results of the study indicate that the formation of a sakinah mawaddah warahmah family character is the responsibility of all family members based on faith and piety to Allah SWT and the example of the Prophet Muhammad SAW. The objectives of family formation in Islam include protecting the family from the torment of hell, worshiping Allah SWT, forming noble character, and nurturing family members especially children to have individual, social, and professional strength. A sakinah mawaddah warahmah family is characterized by peace of mind, love, and the mercy of Allah SWT, which is manifested through increased faith and piety, cooperation between husband and wife, and the instilling of values of honesty, discipline, deliberation, and love. Therefore, it is important to instill these values from an early age, especially for the younger generation before they enter family life.